Triffin reloaded: The matrix of contradictions around global quasi-state money - Herman M. Schwartz (Max Planck Institute for the Study of Societies, 2024)
What explains the US dollar's role in the global economy and the tensions affecting its likely persistence? Most analyses start from Triffin's dilemma, which accurately captured specific but partial tensions of a global monetary system based on essentially fixed exchange rates, gold backing for its core currency, and relatively robust capital controls. Triffin's approach, and those based on it, struggles to explain the tensions in a system with floating exchange rates and fiat money, because Triffin and successors assume a commodity theory of money, a loanable funds model for credit creation, and the "triple coincidence" of monetary, legal, and economic zones. Approaching the question from different premises - chartalist money, endogenous credit creation, and interlocked global balance sheets - enables us to see four factors behind the antinomies or dilemmas that structure the dynamics and durability of US dollar centrality. Those four factors are adequate credit creation and thus global aggregate demand growth, current account deficits for the core, domestic legitimacy in major economies, and the dollar's status as global quasi-state money. – – Wie lässt sich die Bedeutung des US-Dollars in der Weltwirtschaft erklären? Was hat das mit den Spannungen auf sich, die über den Fortbestand der Dollar-Dominanz entscheiden? Die meisten Analysen nehmen das Triffin-Dilemma zum Ausgangspunkt, das spezifische Spannungen des globalen Geldsystems einst gut erfasste. Dieses System basierte im Wesentlichen auf festen Wechselkursen, einer goldgedeckten Leitwährung und Kapitalverkehrskontrollen. Triffins Ansatz und darauf aufgebaute Analysen haben aber Schwierigkeiten, wenn es um die Spannungen in einem Geldsystem mit Fiatgeld und frei schwankenden Wechselkursen geht. Triffin und seine Nachfolger nahmen die Warentheorie des Geldes und das Loanable-Funds-Modell der Kreditschöpfung als stimmig und die dreifache Koinzidenz von Währungs-, Rechts- und Wirtschaftsräumen als gegeben an. Wenn wir das Problem hingegen unter den Prämissen des chartalistischen Geldes, der endogenen Kreditschöpfung und miteinander verzahnter globaler Bilanzen betrachten, lassen sich hinter den Unvereinbarkeiten und Dilemmata vier Faktoren erkennen, die für die Dynamiken und die Dauerhaftigkeit der Dollar-Dominanz entscheidend sind: eine angemessene Kreditschöpfung und damit ein Wachstum der globalen Gesamtnachfrage; Leistungsbilanzdefizite der Kernländer; innenpolitische Legitimität in den großen Volkswirtschaften; und der Status des Dollars als globales Quasi-Staatsgeld.
hdl:21.11116/0000-000F-5796-6
Keywords: 300; Balance of payments; foreign debt; geo-economics; international financial system; money; power; reserve currency; Auslandsverschuldung; Geld; Geoökonomie; internationales Finanzsystem; Leitwährung; Macht; Zahlungsbilanz